Butterfly: Resisting the harms of anti-trafficking policies and fostering peer-based organising in Canada - Lam, Elene; Lepp, Annalee (Anti-Trafficking Review, 2019)
Drawing on knowledge gleaned from over four years of community organising and from the ongoing compilation of the experiences of Asian and migrant sex workers in Canada, this article presents a case study of the work of Butterfly, a migrant sex worker-led and sex worker-focused organisation. It explores how Butterfly, through various mediums, has sought to challenge the discourses, laws, and policies that negatively impact Asian and migrant sex workers. It also highlights how the organisation, through its peer-based model and activities and its radical centring of the voices and experiences of Asian and migrant sex workers, is able to more effectively address their everyday realities and struggles. In this way, Butterfly offers a grassroots alternative to the often detrimental prohibitionist and anti-trafficking interventions undertaken by governments, law enforcement, and social service organisations.